Experience in using the combined method "Rendezvous" in interventions on the distal biliary tract - R. R. Mudarisov; D. Yu. Komissarov; R. M. Nagaev; A. Kh. Mnoyan; I. V. Yangirov; G. A. Starkov; Z. A. Gasanbekov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
The article presents our own experience of observation during interventions on the distal biliary tract using a combined method – "Rendezvous" in patients with pathology of the pancreatobiliary zone, complicated by obstruction of the bile ducts. In one case, with a pronounced adhesive process of the abdominal cavity with a surgical aid, the endoscope was carried out to the descending branch of the duodenum. Towards the endoscope through the stump of the cystic duct, a conductor string was brought down, which made it possible to visualize the major duodenal papilla (MDP), to perform retrograde papillosphincterotomy with choledocholithotomy. In the second case, if it was impossible to pass the guidewire retrogradely beyond the area of the tumor narrowing, an alternative method was used – bringing it down by percutaneous transhepatic access towards the endoscope to install a retrograde stent delivery system.